São Tomé and Príncipe : A Country Economic Memorandum - World Bank (Washington, DC, 2013)
This report assesses the progress made by Sao Tome and Principe over the past decade, and presents a set of recommendations on policy and institutional change that might help the economy perform better in the future. This exercise is important, on one hand, in light of the need to manage the country's higher income expected shortly from its oil resources so as to make it the basis of permanent improvement in the lives of its people. After the Introduction, Chapter 2 reviews the country's recent reform and policy initiatives, its macroeconomic and sectoral performance, and the effectiveness of public policy during the later 1990s. Chapter 3 outlines the constraints to private-sector-led growth. It also analyzes the two sectoral sources that hold the most promise for economic diversification; agriculture and tourism. Chapter 4 examines the main economic development challenges the country faces in achieving growth and poverty alleviation: human resource development, economic management, continued institutional reforms, and capacity building. It provides medium-term recommendations for policy reforms to underpin the process of efficient and sustained growth and poverty reduction. In Chapter 5, macroeconomic projections provide an indication of Sao Tome's medium-term prospects.